Feedforward consequences of isometric contractions: effort and ventilation. Issue 15 (1st August 2016) - Luu, Billy L.; Smith, Janette L.; Martin, Peter G.; McBain, Rachel A.; Taylor, Janet L.; Butler, Jane E.
Abstract: The onset of voluntary muscle contractions causes rapid increases in ventilation and is accompanied by a sensation of effort. Both the ventilatory response and perception of effort are proportional to contraction intensity, but these behaviors have been generalized from contractions of a single muscle group. Our aim was to determine how these relationships are affected by simultaneous contractions of multiple muscle groups. We examined the ventilatory response and perceived effort of contraction during separate and simultaneous isometric contractions of the contralateral elbow flexors and of an ipsilateral elbow flexor and knee extensor. Subjects made 10‐sec contractions at 25, 50, and 100% of maximum during normocapnia and hypercapnia. For simultaneous contractions, both muscle groups were activated at the same intensities. Ventilation was measured continuously and subjects rated the effort required to produce each contraction. As expected, ventilation and perceived effort increased proportionally with contraction intensity during individual contractions. However, during simultaneous contractions, neither ventilation nor effort reflected the combined muscle output. Rather, the ventilatory response was similar to when contractions were performed separately, and effort ratings showed a small but significant increase for simultaneous contractions. Hypercapnia at rest doubled baseline ventilation, but did not affect the difference in perceived effort between separate and simultaneous contractions. The ventilatory response and the sense of effort at the onset of muscle activity are not related to the total output of the motor pathways, or the working muscles, but arise from cortical regions upstream from the motor cortex. Abstract : Our aim was to determine how the relationships between ventilation and perception of effort are affected by simultaneous contractions of multiple muscle groups. We examined the ventilatory response and perceived effort of contraction during separate and simultaneous isometric contractions of the contralateral elbow flexors and of an ipsilateral elbow flexor and knee extensor. The ventilatory response and the sense of effort at the onset of muscle activity are not related to the total output of the motor pathways, or the working muscles, but arise from cortical regions upstream from the motor cortex.